2016
DOI: 10.1016/j.anpedi.2015.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Asociaciones de probióticos para la prevención de la enterocolitis necrosante y la reducción de la sepsis tardía y la mortalidad neonatal en recién nacidos pretérmino de menos de 1.500 g: una revisión sistemática

Abstract: Probiotics are a beneficial tool in the prevention of NEC and mortality in preterm neonates. Moreover, the combination of 2 probiotics (Lactobacillus acidophilus with Bifidobacterium bifidum) seems to produce the greatest benefits. However, due to the differences in probiotic components and administration, it would be wise to perform a randomised controlled trial comparing different probiotic mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It has been shown that probiotics can restore intestinal micro-ecological balance, repair the intestinal membrane barrier, improve intestinal colonization, and inhibit the excessive growth of opportunistic pathogens [ 24 ]. Probiotics help to decrease NEC, late-onset sepsis, and the mortality of preterm infants [ 25 ]. It is suggested that the status, the gene phenotype, and the gut microbiota of pregnant women, as well as the delivery mode, could influence the establishment and construction of gut microbiota in newborns [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that probiotics can restore intestinal micro-ecological balance, repair the intestinal membrane barrier, improve intestinal colonization, and inhibit the excessive growth of opportunistic pathogens [ 24 ]. Probiotics help to decrease NEC, late-onset sepsis, and the mortality of preterm infants [ 25 ]. It is suggested that the status, the gene phenotype, and the gut microbiota of pregnant women, as well as the delivery mode, could influence the establishment and construction of gut microbiota in newborns [ 26 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest meta-analysis had an obvious lack of effect of probiotics in ELBW infants, on the prevention of sepsis, and on the use of a specific probiotic strain. A meta-analysis by Baucells et al [72] included 9 studies pooling a total of 3,521 newborns and found that probiotics administration was associated with a reduced risk of NEC (RR 0.39; 95% CI 0.26-0.57) and mortality (RR 0.70; 95% C 0.52-0.93), with no difference to placebo regarding late-onset sepsis (RR 0.91; 95% CI 0.78-1.06).…”
Section: Discussionmentioning
confidence: 99%
“…Language was not restricted. Additional strategies to identify studies included manual review of reference lists of key articles that fulfilled our eligibility criteria, use of the “related articles” feature in PubMed, use of the “cited by” tool in Web of Science and Google Scholar, and manual review of reference lists of meta-analyses on probiotics in preterm infants [ 23 , 24 , 25 , 27 , 28 , 30 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The search method used to identify all relevant articles was discussed and developed by two authors (EV-M and EV) and the final search string was approved by all authors.…”
Section: Methodsmentioning
confidence: 99%